Uji Aktivitas Soyghurt Ekstrak Daun Pucuk Merah (Syzygium myrtifolium [Roxb] Walp.) dan Soyghurt Ekstrak Bunga Telang (Clitoria ternatea L.) Terhadap Bakteri Escherichia coli - Susanti, Susanti; Afriliani, Sindy; Mardianingrum, Richa (Jurnal Farmasi & Sains Indonesia, 2023)
Diarrhea is a disease characterized by changes in the form of feces and an increase in the frequency of bowel movements that are more frequent than usual. One of the causes of diarrhea is infection by Escherichia coli which is a normal microflora in the human large intestine that helps the process of food spoilage, but can be pathogenic if the number increases. Red shoot leaves (Syzygium myrtifolium [Roxb] Walp.) and butterfly pea (Clitoria ternatea L.) contain anthocyanins, which are compounds derived from flavonoids which have antibacterial properties. The purpose of this study was to determine the presence of antibacterial activity in soyghurt preparations with a combination of red shoots and soyghurt leaf extract with a combination of butterfly pea flowers, and to determine the most effective concentration for inhibiting the growth of Escherichia coli bacteria using the well-diffusion method. The results showed that soyghurt red shoots leaf extract had antibacterial activity against Escherichia coli bacteria with an inhibition zone diameter of 4.60 mm at a concentration of 10% and 7.95 mm at a concentration of 20%. Whereas in soyghurt butterfly pea flower has antibacterial activity against Escherichia coli bacteria with an inhibition zone diameter of 35.35 mm at a concentration of 5%, 38.68 mm at a concentration of 10% and 40.18 mm at a concentration of 20%.